OECD Going for Growth Report - Manus O'Donnell (National Competitiveness and Productivity Council (NCPC), 2021)
Every year, the OECD publishes the Going for Growth report, which identifies structural reform priorities to boost medium-term economic growth in an inclusive and sustainable way. This year - the OECD has identified five priority areas for Ireland: improving labour force participation; boosting housing supply; easing barriers to competition; expanding healthcare coverage; and addressing climate change. The NCPC will review these areas - and the specific policy actions recommended by the OECD - in the preparation of the Council's flagship annual publication, the Competitiveness Challenge.
Keywords: 330